The Effect of Irisin Hormone on Motor Function in Thorocal Spinal Cord Injury Model - Dogru, Meryem Sedef; Yilmaz, Secil; Ozdede, Mehmet Ridvan; Bilek, Furkan; Bulmus, Ozgur; Ercan, Zubeyde (Wiley, 2023)
[Abstract Not Available]
Keywords: Spinal cord injury; Irisin; BBB; Inclined plane